Answer :

yoooojefehf

Answer:

r = 4

Step-by-step explanation:

Answer:

r = 4

Step-by-step explanation:

Our goal is to let the r alone on one side of the equation.

33 = 12r-3(9-r)

First, let's distribute the 3 into the parenthesis:

33 = 12r - 3*9 - 3*(-r)

33 = 12r - 27 + 3r

Now we add 27 on both sides of the equation

33 + 27 = 12r - 27 + 3r + 27

60 = 12r + 3r

Now that we only have terms with r on the right side, we can sum them

60 = 15r

We divide by 15 on both sides

60/15 = 15r/15

4 = r

Other Questions